Social and Economic Factors of Building of National Education in Ukraine (1991–2004) - Kuzmenko, Yuliia (Pedagogical Discourse, 2015)
The article in historical and pedagogical context exposed changes of principles and strategies of development of education of Ukraine; it is outlined transitional processes (from educational system of the USSR to building of proper national system of education); it is focused on the stages of formation and development of national educational system in 1991–2004 years; it is given division into periods of evolution of educatorʼs legislation; it is characterized normative and legal documents of Ukraine that determined educational politics in the State and carrying out of reforms in educational branch by the government; it is defined economic reasons that caused educational crisis of researched period. It is described State power of influence on forming of educational component of peopleʼs capital of specialists in the search of ways of forming of qualified and competitive labor plover, acknowledgement of Ukrainian diplomas on the world labor market, building of educational infra-structure which permitted to use for young generation of workers kept knowledge, skills, habits and experience in its further labor activity on manufacture or in sphere of services. It is coordinated – exhaustion of post Soviet size of functioning of educational system of Ukraine led to reforming of national education, component of which was development of market of educational services and all this was held in a discrepant way. St is exposed dependence of development of educational branch from demands and tendencies of development of social manufacturing. Thanks to analysis of volumes of budget financing of educational of Ukraine with positions of world experience of this question it is established that money of State budget on education have rather low percentage of internal gross product. It is outlined the aspect of historical assessment of educational potential in independent Ukraine, it is given statistical facts (literacy among adults, general quantity of pupils, index of level of education) that were important components in calculations of index of peopleʼs development in Ukraine. It is cutline positive and negative factors that influenced on grafting of level of educational component of peopleʼs capital. It is coordinated that in spite of the fact that in the 90-th years of the XX-th century theory of peopleʼs capital had its supporters in Ukraine, unfortunately practice of inculcation of ideas of investment in peopleʼs capital in 1991–2004 years in general had low realization.